A Detailed Look at a Trio of Changing-look Quasars: Spectral Energy Distributions and the Dust Extinction Test - Laura Duffy; Michael Eracleous; Jessie C. Runnoe; John J. Ruan; Scott F. Anderson; Sabrina Dimassimo; Paul Green; Stephanie LaMassa (The Astrophysical Journal)
Changing-look quasars (CLQs) exhibit dramatic variability in broad emission-line fluxes on short timescales. This behavior is challenging to many models of the quasar broad-line region, due in large part to the short transition times between high and low states. In order to constrain the cause of the dramatic variability, we obtained contemporaneous Hubble Space Telescope ultraviolet and Hobby Eberly Telescope optical spectra of three CLQs caught in their low state. We use these spectra, along with archival spectra taken during both the high and low states, to investigate potential scenarios for the change in state. Our data strongly disfavor a variable dust obscuration scenario for these three CLQs, and instead suggest that the observed transformation reflects a change in the intrinsic luminosity of the central engine. We also find that the low-state spectral energy distributions of all three quasars are reminiscent of those of low-luminosity active galactic nuclei, which suggests that the transition may result from a change in accretion flow structure caused by a reduced Eddington ratio.